ESTIMATION OF DAMAGE LEVELS OF LEAF DEFOLIATOR CATOPSILIA PYRANTHE, IN INDIAN SENNA , IN INDIAN SENNA , IN INDIAN SENNA CASSIA ANGUSTIFOLIA ANGUSTIFOLIA ANGUSTIFOLIA VAHL - VARGHESE, THANIA SARA (The Bioscan, 2016)
The larvae of the mottled emigrant butterfly Catopsilia pyranthe has been reported as a major defoliator in Indian Senna, Cassia angustifolia Vahl where it can causes economic damage to the leaves which is internationally and widely accepted for its medicinal laxative properties. Field experiments were carried out at Directorate of Medicinal and Aromatic Plants Research, Boriavi Anand to find out the larval population of the pest at which economic yield loss can occur. The economic threshold levels (ETL) of the pest were determined in the Senna crop at 45 days after sowing (DAS) and at 75 DAS. At 45 DAS, the ETL level was found to be 3.3 larvae/plant and at 75 DAS 7.9 larvae /plant. Thus, finding the economic threshold level of a pest practically gives an insight about the timely intervention of the management practices.